TBILISI SYMPOSIUM ON THE UNCONSCIOUS - A SHORT RETROSPECTIVE - Imedadze , Irakli (Georgian Psychological Journal, 2022)
Already 40 years have passed since a large-scale Tbilisi international symposium on the unconscious was held, which aroused a great intereﬆ in the psychological community due to the fact that all the major issues related to the unconscious were discussed. A productive dialogue took place between the repre- sentatives of psychoanalysis and Dimitri Uznadze’s school of psychology. The present article highlights the key points of diﬀerence between these two approaches to the unconscious. It also covers some details concerning the preparation of the symposium and the way it was held. Also, the article explains why the symposium was organized in Tbilisi. The above context is used to show that D. Uznadze’s Set Theory is the only general psychological conception in the Soviet psychology which represents a coherent syﬆem of ideas about the unconscious psyche.